Analysis of Power Losses and Voltage Drop in the Parungpanjang–Cilejit LAA Traction Substation for KRL Service Optimization - Mardito Adenovit Kusnanda Putra; Budi Yanto Husodo (Green Publisher Indonesia, 2026)
The increase in the frequency of electric rail train trips on the Tanah Abang–Rangkasbitung line, especially on the Parungpanjang–Cilejit road section, requires the Upper Flow Electricity system to operate at a higher capacity to maintain the continuity of traction electricity supply. This study aims to analyze the existing conditions of the Upper Flow Electricity system, identify the technical factors that affect power loss and voltage drops, and evaluate several alternative solutions that can be applied to improve the reliability of power distribution. It used quantitative approach based on manual calculations using technical parameters such as the length of the trajectory between substations, conductor resistance, load current, and nominal voltage. Two alternative solutions were analyzed, namely the insertion of traction substations at strategic points to shorten the supply distance, as well as improving the technical specifications of the upstream power grid through the replacement of conductor size and configuration and increasing substation capacity. The calculation results show that, in the existing condition on the 8-minute headway, the voltage drop reached 239.256 V (14.77%) and the power loss was 268.813 kW. The alternative application of substation insertion lowered the voltage drop to 103.243 V (6.37%) and the power loss to 111.323 kW, while the alternative of increasing technical specifications resulted in a voltage drop of 140.958 V (8.7%) and a power loss of 134.406 kW. Both alternatives show significant potential in reducing power loss and keeping voltage within safe limits, so they can serve as problem-solving steps on this line.